Ground beetle assemblages inhabiting various age classes of Norway spruce stands in north-eastern Poland - Mariusz Nietupski; Agnieszka Kosewska; Emilia Ludwiczak (PeerJ, 2023)
Assemblages of epigeic ground beetles living in Norway spruce forests in north-eastern Poland in three age ranges: young: 20–30 years (A); middle-aged: 40–50 years (B); old: 70–80 years (C) were investigated. In each age category, 4 plots with 5 Barber traps were set up. Ground beetle assemblages were compared in terms of their abundance, species richness, and the Shannon H’ index value. Quantitative ecological description of the carabids captured in the analysed age-classes of Norway spruce forests was performed, and the values of the mean individual biomass (MIB) were calculated. To determine the correlation between mean individual biomass and abundance of various ecological groups of carabid beetles, the Spearman rank correlation coefficient was calculated. The assemblages of ground beetles living in the Norway spruce forests in north-eastern Poland were characterised by quite large species richness (44 species in total). There were significant differences in species richness among the different ages of Norway spruce forests. The oldest Norway spruce stands (70–80 years old) had a smaller number of species and specimens of ground beetles as well as the highest MIB values in comparison with the younger spruce forests A and B. The results revealed that high MIB values were positively correlated with the presence of large ground beetle species with higher moisture requirements. Lower values of the MIB index were due to the presence of smaller open habitat macropterous species, with the spring type of breeding and associated with open areas.